Leading source and constraint on the systematic spread of the changes in East Asian and western North Pacific summer monsoon - Shijie Zhou; Ping Huang; Gang Huang; Kaiming Hu (Environmental Research Letters, 2019)
With ongoing global warming, the changes in EA-WNPSM rainfall—feeding over two billion people in East Asia and the Indochina Peninsula—projected by the Coupled Model Intercomparison Project Phase 5 (CMIP5) models show remarkable and unidentified inter-model spread. Here, we reveal the leading inter-model spread of EA-WNPSM changes in 28 CMIP5 models is related to a ‘dry north–wet south’ dipole in East Asia and a wet Indochina and WNP. This spread pattern of EA-WNPSM changes is induced by the spread of sea surface temperature changes in the equatorial western Pacific, and can be further traced back to an apparent discrepancy among the state-of-the-art models in simulating the tropical Pacific rainfall. An air-sea coupling processes involved with summer background circulation contribute to this robust spread pattern of EA-WNPSM changes. We can constrain the EA-WNPSM rainfall changes based on the current-future relationship and observation that there should be more rainfall increase in North China and the Korean Peninsula and less increase in South China, the Indochina Peninsula and WNP, relative to previous multi-model ensemble projections.